The Tatar Volost of Kasimov Uyezd of Ryazan Province in the 1920s through the Context of Soviet Nation-Building - Gallyamova, Alfiya G.; Khanipova, Il’nara I. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
Аbstract: The authors examine the history of the Kasimov Tatars’ struggle to preserve the Tatar volost in the Kasimov district of the Ryazan province. The authors reflect upon the unstable political situation of the 1920s, during the implementation of the Soviet nationbuilding process, and highlight the conflict between proponents and opponents of the national factor in the administrative and regional restructuring of the Soviet state. Based on a wide range of sources, many of which are introduced into scientific circulation for the first time, the text of the work sheds light on the twists and turns in the process of the liquidation and revival of the Tatar volost throughout the 1920s. The authors demonstrate the presence of serious multipolar discourse through the deconstruction of the old model of state organization. The pragmatic considerations of the central authority, driven by the desire to increase management efficiency in regions with concentrated ethnic minority populations, interacted with the sociopolitical demands of the Kasimov Tatars, who demonstrated cohesion and organization in defending their national status rights. The consolidated actions of the Kasimov Tatars were directed against the uyezd and gubernia official structures, which were staffed by individuals who were unsympathetic to the idea of politicalethnic structuring of Russian territories. The content of the study leads to the conclusion that the Kasimov Tatars actively engaged in the ethnopolitical processes of the 1920s.